(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
Emergencies and treatment of surgical complications constitute the bulk of surgical activities in developing nations as against elective surgeries. A significant reduction in surgical disease burden is feasible in local communities using simple but effective options. An account is presented of such a service offered through an outreach program conducted over three months period among the rural populace of Southern Nigeria. We did a descriptive retrospective study of 152 consecutive patients who had elective repair of groin hernia between March – June 2019. Patients presented on their own volition in response to the publicity given to the outreach program by the local organizers. There were a total of 174 groin hernia repairs were done in 152 patients including 22 (14.5%) bilateral lesions. Inguinal hernia was by far the most common groin hernia constituting 171 (98.3%) against femoral hernia recorded only in 7 (4%). More males were affected by inguinal hernia than females but the reverse was the case for femoral hernia. Approximately three quarter of the patients harboured their symptoms for more than one year due to financial constraints in 71.3% of patients. However, in a medical outreach program, financial burden is removed. So in resource poor setting, elective hernia repair uptake is therefore enhances.